Klasifikasi Akreditasi Sekolah Di Kota Jambi Menggunakan Metode Naïve Bayes Di Bpmp Jambi - Agnes Febrin Sitanggang; Errisya Rasyawir; Aryani, Lies (LPPM Universitas Dinamika Bangsa, 2024)
Accreditation is the awarding of a predicate to a school with the aim of improving and also obtaining an overview of development, quality improvement and determining a school as an education provider. School accreditation is an important factor in improving the quality of education. Assessments are also carried out systematically and comprehensively by passing evaluations by authorized institutions. Schools will get an accreditation title if they meet predetermined standards. Classification is one of the data mining techniques that can be used in the process of classifying school accreditation. The test was carried out by using 2 options tests, namely the Use Training Set and 10 Fold Validation. Data testing with the best percentage is 99% using the Use Training Set. Therefore the Naïve Bayes algorithm is an algorithm that is quite effective and good in calculations and final results.